Learning to Cope: A CBT Evaluation Exploring Self-Reported Changes in Coping with Anxiety Among School Children Aged 5–7 Years. (16th October 2018) - Ruocco, Sylvia; Freeman, Nerelie C.; McLean, Louise A.
Abstract : This study examined the effects of a school-based cognitive-behavioural group intervention for anxiety in young children, Get Lost Mr Scary, on child self-reported anxiety and coping skills. Participants included 65 children ( M age = 6.50 years, SD age = 0.75) drawn from 13 public primary schools located in Western Sydney, Australia. The children participated in seven weekly 1-hour Get Lost Mr Scary sessions, and their parents attended three information sessions. The pictorial semistructured Child Anxiety and Coping Interview (CACI) was used to elicit the children's self-report of their anxiety symptoms, emotions, coping strategies, and coping efficacy before and after the 7-week intervention. Although children rated their maladaptive coping strategies as helpful, the postintervention results indicated a significant decrease in the use of maladaptive strategies such as behavioural avoidance and an increase in adaptive cognitive strategies, particularly cognitive restructuring. Consistent with parent and teacher reports, child self-reports indicated a significant reduction in anxiety and negative emotional distress. The clinical implications of the findings are discussed.